Neuropsychology of Communication - Balconi, Michela; SpringerLink (Online service) (Milano : Springer Milan, 2010)
The volume focuses on the neuropsychological correlates of communication in daily interactions. The predominant account in explaining the construction of meaning by humans is the inter-relational perspective, which postulates an intentional convergence of meaning arising as a consequence of the active exchanges between people. The neural correlates of communication are described on the basis of new empirical results, with particular focus on language and language development, pragmatics and neuropragmatics of communication, neurocognition and the cognitive bases of intentions, nonverbal communication and emotion contribution to communicative systems. In addition, new methodological approaches are described, such as neuroimaging (PET and fMRI), and brain stimulation techniques (MEG and TMS), as well as their applications in research and in the clinical field.
The Neuropsychology of Language and Communication -- Biological Basis of Linguistic and Communicative Systems: From Neurolinguistics to Neuropragmatics -- Methods and Research Perspectives on the Neuropsychology of Communication -- Transcranial Magnetic Stimulation in the Study of Language and Communication -- Electromagnetic Indices of Language Processing -- Neuropragmatics. Psychophysiological, Neuropsychological and Cognitive Correlates -- From Pragmatics to Neuropragmatics -- Idiomatic Language Comprehension: Neuropsychological Evidence -- Anticipatory Mechanisms in Idiom Comprehension: Psycholinguistic and Electrophysiological Evidence -- Towards a Neurophysiology of Language -- From Intentions to Nonverbal Communication -- Intentions and Communication: Cognitive Strategies, Metacognition and Social Cognition -- The Neuropsychology of Nonverbal Communication: The Facial Expressions of Emotions -- Emotions, Attitudes and Personality: Psychophysiological Correlates.
Keywords: Medicine; Speech pathology; Medicine & Public Health; Medicine/Public Health, general; Speech Pathology; Linguistics (general).